Cross sectional study to assess immunization knowledge and practice among families of children between 0 -5 years in rural areas of Punjab, India - Khurana, Mandeep Singh; Malik, Supriya; Arora, Sunita (International Journal of Contemporary Pediatrics, 2017)
Background: Immunization is the single most cost effective and efficient intervention to reduce the burden of childhood mortality and morbidity worldwide. Vaccines under universal immunization programme (UIP) are provided free of cost but still the current coverage of fully immunized children is quite low. Main reason identified for poor coverage included illiteracy, lack of knowledge and poverty. Methods: It is a cross sectional study carried out in rural area of Punjab from March 2014-March 2015. Total 500 families with 500 children between age 0-5 years were selected randomly. Study involved one to one, interview according to a pretested structured questionnaire prepared in a vernacular language Punjabi and English too. Results: Total 500 children were included in the study out of which 230 (46%) were female and 270 (54%) were male. Maximum coverage to BCG vaccination (77.2%) and minimum for measles vaccine (56.2%) was observed. 55% of children were completely immunized, 28.8% were partially immunized and 16.2% were not immunized. Most common reason given by families for nonimmunization was lack of knowledge, family issues and sickness of child. Conclusions: It is concluded from present study that the main reason for partial on-immunization was lack of knowledge of families about vaccination. Considering incomplete knowledge and inappropriate practices the policy makers and medical profession require to put in much more efforts to sensitise families about importance regarding immunization in preventing diseases and their consequent morbidity and mortality.